PENYELESAIAN PERUSAHAAN PEMBIAYAAN KONSUMEN DALAM HAL DEBITUR WANPRESTASI PADA SUZUKI FINANCE CABANG DENPASAR - Sugiharta Wardana, I Komang; Wita, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 03, Juni 2014, 2014)
Related to rampant cases of defaults that occurred in recent years, particularly between the debtor and consumer finance companies. Thus it will be discussed what criteria can be used by a consumer finance company in determining the debtor is in default and how the process of resolving the problem of default. The method used is an empirical legal research with interview data collection techniques. The conclusion of this study indicate that the process of settlement of the problem of default that occurred on Suzuki Finance Branch Denpasar already done as it should be based on criteria that have been set.
Keywords: Default, Financing, Consumer, Debtor